Genome‐wide cooperation of EMT transcription factor ZEB1 with YAP and AP‐1 in breast cancer. (21st July 2020) - Feldker, Nora; Ferrazzi, Fulvia; Schuhwerk, Harald; Widholz, Sebastian A; Guenther, Kerstin; Frisch, Isabell; Jakob, Kathrin; Kleemann, Julia; Riegel, Dania; Bönisch, Ulrike; Lukassen, Sören; Eccles, Rebecca L; et al.
Abstract: Invasion, metastasis and therapy resistance are the major cause of cancer‐associated deaths, and the EMT‐inducing transcription factor ZEB1 is a crucial stimulator of these processes. While work on ZEB1 has mainly focused on its role as a transcriptional repressor, it can also act as a transcriptional activator. To further understand these two modes of action, we performed a genome‐wide ZEB1 binding study in triple‐negative breast cancer cells. We identified ZEB1 as a novel interactor of the AP‐1 factors FOSL1 and JUN and show that, together with the Hippo pathway effector YAP, they form a transactivation complex, predominantly activating tumour‐promoting genes, thereby synergising with its function as a repressor of epithelial genes. High expression of ZEB1, YAP, FOSL1 and JUN marks the aggressive claudin‐low subtype of breast cancer, indicating the translational relevance of our findings. Thus, our results link critical tumour‐promoting transcription factors: ZEB1, AP‐1 and Hippo pathway factors. Disturbing their molecular interaction may provide a promising treatment option for aggressive cancer types. Synopsis: How the EMT‐transcription factor ZEB1 stimulates cancer cell plasticity in context‐dependent manner is unclear. Here, genome‐wide analyses highlight AP‐1 and Hippo effector YAP as novel binding partners of ZEB1, cooperating in driving tumour‐promoting gene expression in mammary malignancies. ZEB1 and AP‐1 factor JUN co‐occupy DNA‐targets in human TNBC cells. ZEB1 directly interacts with AP‐1 factors JUN and FOSL1. ZEB1 mediates dual transcriptional function, being repressive on its own, but trans‐activating together with AP‐1 and YAP. ZEB1, AP‐1 and YAP correlate with worse survival in claudin‐low aggressive breast cancer. Abstract : Aggressive cellular states in human breast cancer are defined by context‐dependent interplay between transcriptional regulators ZEB1, AP‐1 and YAP.